A Continuous 13.3-Ka Paleoseismic Record Constrains Major Earthquake Recurrence in the Longmen Shan Collision Zone - Shi, Wei; Jiang, Hanchao; Alsop, G. Ian; Wu, Guo (Frontiers in Earth Science, 2022)
Thrust collision zones with low slip rates along the plate boundary are significant areas of stress accumulation and prone to develop more destructive earthquakes with longer recurrence intervals. Such regions are often classified as low seismic risk if they lack continuous records of large earthquakes, such as the eastern Tibetan Plateau before the 2008 Mw 7.9 Wenchuan earthquake. Here, we provide a continuous seismic record in the Longmen Shan thrust fault zone spanning 13,000 years based on detailed investigation of the soft-sediment deformation structures and seismites in the Lixian lacustrine sequence. The recurrence time of large earthquakes (M ≥ 8.1) is 1,200 years, which is significantly shorter than the previous estimate of 2,000–6,000 years. The Maoxian-Wenchuan fault is the main fault that triggered the deformation in the Lixian lacustrine sediments. In addition, earthquake recurrence in the warm period is more frequent than that in the cold period, which should arouse our attention for the seismic study of tectonically active regions.